Efektifitas Daun Kersen (Muntingia Calabura L.) Terhadap Profil Histologi Tikus Putih Jantan (Rattus Norvrgicus) Diabetes Mellitus - Telaumbanua, David Charles; Erida Novriani; Razoki (CV. ITTC INDONESIA, 2025)
Diabetic mellitus (DM) is a degenerative condition marked by high blood suger levels brought on by a malfunction in the metabolisme of insulin. Serious side effect, such as harm to organs including the pancreas can result from uncontrolled diabetes mellitus the use of medicanal plants, such the kersen leaf (Muntingia calabura L.), which includes active substances like flavonoids, alkaloids, saponins and tannins whith possible antidiabetetic effects, is one altenate therapy option that is presently being investigated. Using male white rats (Rattus norvegicus) with diabetes, this study intends to assess the impact of an ethanolic extract of (Muntingia calabura L.) leaves on the pancreas and identify the optimal dosage for mitigating pancreatic cell damage. Five groups are used in this pure experimental study: three treatment groups that get extract doses of 150,300 and 600 mg/kgBW; a positive control that receives glibencalmide; and a negative control that receives Na CMC. Assessments were made of pancreatic histology and blood glucose levels. The results should offer scientific validation for the long-standing practice of using cherry leaves to treat diabetes.